O mosaico de Helder Macedo : as relações entre história e ficção em Vícios e virtudes - Fernandes, Patrícia Fátima Soares (2016)
This research seeks to understand the recurrence of past redemption and the revisiting of national history, in the literary work Vícios e Virtudes (2002), by Helder Macedo. We intend to analyze and question what is actually history and what is fiction, as well as observe how a speech interfere each other, causing different interpretations of historical facts that form the identity of the Portuguese people. From this, we can question how identity is seen in the postmodern literary context, especially when it is supported by a myth like sebastianism. We found in the literary text by Macedo aspects that allow us to discuss hidden truths and cultural issues rooted in the literary imaginary. To mediate the study of the borders between history and literature we will use the notion of historiographical metafiction proposed by Linda Hutcheon (1991).